Square both sides, then solve.
sqrt(5u+10) = sqrt(9u+7)
(5u+10) = (9u+7)
5u-9u=7-10
-4u=-3
u=3/4
2007-10-17 23:47:46
·
answer #1
·
answered by Runa 7
·
0⤊
0⤋
One more solution:
Sq root (5u + 10) = Sq root(9u + 7)
By squaring both side
+/-(5u+10)=+/-(9u+7)
By taking + in LHS and - in RHS
5u+10= -9u-7
=> 14u = -17
=> u= -17/14
2007-10-17 23:58:11
·
answer #2
·
answered by Anonymous
·
0⤊
1⤋
sqrt (5u + 10) = sqrt (9u + 7)
^2 both sides...
5u + 10 = 9u + 7
10 = 4u + 7
3 = 4u
u = 3/4 (Result)
2007-10-17 23:50:18
·
answer #3
·
answered by Doctor Q 6
·
1⤊
0⤋
_/(5u + 10 = _/(9u + 7)
Square both sides of the equation to remove the radical sign
5u + 10 = 9u + 7
4u = 3
u = 3/4
2007-10-17 23:55:23
·
answer #4
·
answered by Anonymous
·
0⤊
0⤋
if you're square root-ing the whole expression then
sqr rt of 5u+10=sqr rt of 9u+7
(sqr rt of 5u+10)^2=(sqr rt of 9u+7)^2
5u+10=9u+7
10-7=9u-5u
3=4u
u=3/4
just my hunch, haha! XD
2007-10-17 23:50:49
·
answer #5
·
answered by ylsel1218 1
·
0⤊
0⤋
This last reply is wrong. No +/- here
All the above forgot to check if this value, that is actually right, is really a root of the equation
You have to study the expression's domain or, at least, plug the value in the expression and see if it really is a root
Example
From
x-1 = 2x+1
I get
x = -2
But, from V(x-1) = V(2x+1), if I square, I get this equaion and this root, while V(x-1), when x = -2, doesn't even exist in R
Ilusion
2007-10-18 04:02:17
·
answer #6
·
answered by Ilusion 4
·
0⤊
0⤋
square both sides to get
5u+10 = 9u+7 then
-4u = -3 and
u = 3/4
Doug
2007-10-17 23:49:32
·
answer #7
·
answered by doug_donaghue 7
·
1⤊
0⤋
sqrt(5u+10)=sqrt(9u+7)
(5u+10)=(9u+7)
10-7=9u-5u
3=4u
3/4=u or u=.75
2007-10-17 23:54:09
·
answer #8
·
answered by alecxz 1
·
0⤊
0⤋